Interactional approach of cantilever pile walls analysis - Škrabl, Stanislav (Acta geotechnica Slovenica, 2006)
This paper proposes a new method for the geomechanical analysis and design of cantilever retaining structures. It is based on the limit equilibrium method, but it uses some additional conditions for interaction between the retaining structure and the ground, when referring to the distribution of the mobilized earth pressures on the structure. The greatest benefit of the proposed method is shown in the analysis of structures of layered ground (heterogeneous above the dredge level and homogeneous below it), embedded in frictional and cohesive materials, and in the possibility of considering the influence of surcharge loadings on the active or passive side of the retaining structure. When analyzing such cases in practice, the proposed method gives results which are in better agreement with the results of FEM based elasto-plastic interaction analyses than with the results of currently used methods. At the same time, its results are in accordance with those published for homogeneaus cohesionless ground. Since in practice almost all retaining structures are erected in layered ground (heterogeneaus above the dredge level and homogeneous below it), the proposed method is very convenient and applicable for the analyses and design of cantilever structures under arbitrary geomechanical conditions.
Keywords: analize; geomehanika; metode; podporne konstrukcije